P224 Relationship of faecal calprotectin and long-term outcomes in Finnish adult patients with Crohn's disease: Retrospective multi-centre chart review study. (16th January 2018) - Hallinen, T; Jussila, A; af Björkesten, C -G; Kemppainen, H; Soini, E; Mankinen, P; Valgarðsson, S; Veckman, V; Nissinen, R; Molander, P
Abstract: Background: Fecal calprotectin (fCal) has been shown to correlate well with endoscopic healing in Crohn's disease (CD) patients, while less evidence is available on the association of fCal and long-term outcomes such as the need for surgeries. This study was established to analyse whether the surgery free survival (SFS) is associated with the attained fCal-levels 12 months after biological therapy initiation. In addition, the association of fCal-levels at 12 months and composite event free survival (CEFS) was assessed. The composite event was defined as surgical procedure, corticosteroid initiation, treatment failure, or dose increase occurring after the 12-month fCal-measurement. Methods: A non-interventional, retrospective patient chart review study was carried out in 4 major Finnish gastroenterology clinics (EUPAS17190 registration). The study included adults (age≥18 years) with confirmed CD diagnosis, who had initiated a biologic therapy for CD at any time between January 1 st 2010 and June 30 th 2016 ( n = 186). Results: At the start of follow-up, the patients were on average 44 years old and 49% of them were female. Most of the patients had ileocolonic, non-stricturing/non-penetrating CD. At baseline the mean fCal was 958 mg/g ( n = 62) and at 12-months it was 558 mg/g. The mean follow-up time was 1119 days (range 562–1774). CRP, thrombocytes and albumin levels had strong and significant associations with fCal when measured at similar timepoints. The SFS analysis included 4 failures (i.e. surgical procedures) with the mean of 741 days at risk per patient. fCal (mg/g) at 12 months and ileocolonic CD were significant predictors for SFS. The CEFS analysis included 22 failures with the mean of 572 days at risk per patient. fCal (mg/g) at 12 months was the only significant and robust predictor for CEFS in univariate (HR 1.0005, 95% CI 1.0002 – 1.0008, p = 0.003) and multivariate models. Conclusions: Among the CD patients, fCal was a robust predictor of composite outcome measured as surgical procedure, corticosteroid initiation, treatment failure or dose increase. fCal was also associated with surgery-free survival.